Pematahan Dormansi Benih Kemiri (Aleurites moluccana, L. Willd) yang Direndam dengan Zat Pengatur Tumbuh Organik Basmingro dan Pengaruhnya terhadap Viabilitas Benih - Husain, Indriati; Tuiyo, Rully (Jurnal Agroteknotropika, 2012)
This study aims to determine the breaking dormancy of candleberry seeds which soaked with organic growth regulator Basmingro and its effect on seed viability. Research will be carried out in Limba U2, South City, Gorontalo City, for about 6 months. The materials used are candleberry seeds, organic PGR Basmingro. Candleberry seed soaked in a solution of organic PGR Basmingro in 5 treatment concentration (control (without PGR); PGR 0.02%, 0.03%, 0.04% and 0.05%) and 4 replications. Data were analyzed quantitatively by using Environmental Design Complete Randomized Design (CRD) and analysis of variance (ANOVA). Data are significantly different tested further by Duncan Multiple Rate Test (DMRT). The results are not significantly different, because no germination of candleberry seeds, caused by yet influential PGR is treated to break dormancy due to hard seed coat seed candleberry. So that further research needs to be done by increasing the dose and duration of soaking candleberry seeds with PGR organic Basmingro.